A strained DNA binding helix is conserved for site recognition, folding nucleation, and conformational modulation - Wetzler, Diana Elena (2009)
Nucleic acid recognition is often mediated by alpha-helices or disordered regions that fold into alpha-helix on binding. A peptide bearing the DNA recognition helix of HPV16 E2 displays type II polyproline (PII) structure as judged by pH, temperature, and solvent effects on the CD spectra. NMR experiments indicate that the canonical alpha-helix is stabilized at the N-terminus, while the PII forms at the C-terminus half of the peptide. Re-examination of the dihedral angles of the DNA binding helix in the crystal structure and analysis of the NMR chemical shift indexes confirm that the N-terminus half is a canonical alpha-helix, while the C-terminal half adopts a 3(10) helix structure. These regions precisely match two locally driven folding nucleii, which partake in the native hydrophobic core and modulate a conformational switch in the DNA binding helix. The peptide shows only weak and unspecific residual DNA binding, 10(4)-fold lower affinity, and 500-fold lower discrimination capacity compared with the domain. Thus, the precise side chain conformation required for modulated and tight physiological binding by HPV E2 is largely determined by the noncanonical strained alpha-helix conformation, "presented" by this unique architecture.